PEMBARUAN ISLAM BIDANG KELUARGA DAN RELEVANSINYA DENGAN TUNTUTAN EGALITER LAKI-LAKI DAN PEREMPUAN - Moh. Zakariya (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam)
AbstrakSebagai agama pembaruan, datangnya Islam telah mengubah berbagai aspek kehidupan. Salah satu yang diperbarui adalah sistem kekeluargaan, dari yang semula patriarkal (mengutamakan kaum laki-laki) diperbarui menjadi bilateral atau parental (memberikan kesempatan sama atau setara bagi laki-laki dan perempuan). Pembaruan lain yang dibawa Islam adalah: 1) sistem kepercayaan, dari yang semula politeis (mengakui banyak tuhan) diperbarui menjadi monoteis (mengakui satu Tuhan), 2) sistem sosial, dari yang semula hirarkis-berstruktur diperbarui menjadi egaliter (sejajar), 3) sistem ekonomi, dari yang semula borjuis-kapitalis diperbarui menjadi sistem ekonomi berkeadilan, 4) sistem tanggung-jawab, dari yang semula kolektif (kesukuan/syu’ubiyah) diperbarui menjadi tanggung jawab yang bersifat individu, dan 5) dasar hubungan antara orang perorang, dari yang semula berdasarkan status sosial dan kelompok menjadi ikatan agama (iman). Berkaitan dengan relevansi pembaruan sistem hukum Islam dengan tuntutan egaliter laki-laki dan perempuan, bahwa pembaruan sistem hukum Islam yang memperbarui sistem hukum jahiliyah telah memberi gambaran bagaimana Islam menghendaki terciptanya kehidupan masyarakat yang baik atau khairo ummah yang berkeadilan dan berkesetaraan (egaliter) dengan memperbarui sistem hukum yang ada sebelumnya. Islam datang pada masyarakat Jahiliyah dengan membawa syari'ah (sistem hukum) yang sempurna sehingga mampu mengatur kehidupan manusia, khususnya bagaimana menjalin relasi yang adil dan egaliter antar individu manusia.Kata Kunci: Pembaruan Sistem Hukum, Hukum Jahiliyah, Tuntutan Kesetaraan. AbstractAs a religion of reform, the arrival of Islam has changed various aspects life. One that is being updated is the kinship system, from which Originally patnarchal (prioritizing men) was renewed to become bilateral or parental (providing equal or equal opportunities for men and women) Other reforms brought by Islam are: 1) belief systems, who were originally polytheists (acknowledging many gods) were renewed to become monotheistsac knowledging one God), 2) social system, from the original hierarchical-structured renewed to be egalitarian (parallel), 3) the economic system, from the original bourgeoisie capitalists are renewed into a just economic system, 4) a responsibility system answered, and what was originally collective (tribal / yu ubiyah) was updated to responsibility of an individual nature, and 5) the basis of the relationship between people per person. and which was originally based on social status and group became religious ties (faith). In connection with the relevance of reforming the Islamic legal system with the egalitarian demands of men and women, that system reform Islamic law which reformed the legal system of jahiliyah has embellished the picture how Islam wants the creation of a good community life or khairo ummah who are just and equal (egalitarian) with the ability to be brave the legal system that existed before it. Islam came to the people of Jahiliyah by bringing variah (legal system) that is perfect so as to be able regulate human life, especially how to establish fair relationships and egalitarian among human individuals. Keywords: Law System Renewal, Jahiliyah Law, Demands for Equality